A consensus framework with different preference ordering structures and its applications in human resource selection. (April 2018) - He, Yue; Xu, Zeshui
Highlights: Construct a consensus framework for different preference ordering structures. Propose aggregation operators to integrate different preference ordering structures. Apply PROMETHEE II to obtain the group preferences. Design a consensus reaching process to improve the consensus degree. Illustrate the consensus framework with human resource evaluation problem. Abstract: In complex decision making environment, since the attitudes, cognitions and knowledge backgrounds of the decision makers are quite different with each other, they may provide preference information with different preference ordering structures such as preference orderings, interval preference orderings and hesitant preference ordering sets. In order to obtain reliable decision results, we propose a consensus framework to help the decision makers to discuss with each other, share knowledge and information, and reach a consensus. Normally, the consensus framework consists of two parts: (1) selection process; (2) consensus process. In the selection process, we propose some aggregation operators to integrate the decision makers' preference information with different preference ordering structures. Then, we apply the PROMETHEE II method to obtain the decision results as the standard of the group preferences. In the consensus process, we put forward the weighted ordering consensus degree to judge if the decision makers reach a consensus. Then, an interaction process is designed to improve the consensus degrees of the decision makers with the process of identification and adjustment. Finally, we illustrate the consensus framework with the human resource evaluation and selection problem of Hongqi Chain.